Effects of Nitrogen Availability on the Antioxidant Activity and Carotenoid Content of the Microalgae Nephroselmis sp - Noémie Coulombier; Elodie Nicolau; Loïc Le Déan; Vanille Barthelemy; Nathalie Schreiber; Pierre Brun; Nicolas Lebouvier; Thierry Jauffrais (Marine Drugs, 2020)
Nephroselmis sp. was previously identified as a species of interest for its antioxidant properties owing to its high carotenoid content. In addition, nitrogen availability can impact biomass and specific metabolites’ production of microalgae. To optimize parameters of antioxidant production, Nephroselmis sp. was cultivated in batch and continuous culture conditions in stirred closed photobioreactors under different nitrogen conditions (N-repletion, N-limitation, and N-starvation). The aim was to determine the influence of nitrogen availability on the peroxyl radical scavenging activity (oxygen radical absorbance capacity (ORAC) assay) and carotenoid content of Nephroselmis sp. Pigment analysis revealed a specific and unusual photosynthetic system with siphonaxanthin-type light harvesting complexes found in primitive green algae, but also high lutein content and xanthophyll cycle pigments (i.e., violaxanthin, antheraxanthin, and zeaxanthin), as observed in most advanced chlorophytes. The results indicated that N-replete conditions enhance carotenoid biosynthesis, which would correspond to a higher antioxidant capacity measured in Nephroselmis sp. Indeed, peroxyl radical scavenging activity and total carotenoids were higher under N-replete conditions and decreased sharply under N-limitation or starvation conditions. Considering individual carotenoids, siphonaxanthin, neoxanthin, xanthophyll cycle pigments, and lycopene followed the same trend as total carotenoids, while β-carotene and lutein stayed stable regardless of the nitrogen availability. Carotenoid productivities were also higher under N-replete treatment. The peroxyl radical scavenging activity measured with ORAC assay (63.6 to 154.9 µmol TE g−1 DW) and the lutein content (5.22 to 7.97 mg g−1 DW) were within the upper ranges of values reported previously for other microalgae. Furthermore, contents of siphonaxanthin ere 6 to 20% higher than in previous identified sources (siphonous green algae). These results highlight the potential of Nephroselmis sp. as a source of natural antioxidant and as a pigment of interest.